PENGOBATAN ALTERNATIF PENYAKIT GAGAL GINJAL DARI TANAMAN OBAT DI INDONESIA - Mia Nuraeni; Putri Aulia; Silvia Mutia Nuri; Anisa Siti Patimah; Fransiska Br Manihuruk; Tharil Argi Sadewa; Yogi Prayoga; Maya Arfania (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Kidney failure is caused when the blood urea is more than 200 mg/dl. This is usually caused by damage to the kidney tissue which reduces kidney mass, which then results in an adaptation process in the form of hypertrophy of the remaining normal kidney tissue and hyperfiltration. This study aims to determine what medicinal plants exist in Indonesia and can be used as alternative medicine for patients with kidney failure. This study uses the Literature Review Article (LRA) method, literature searches are carried out through Google Scholar and Publish or Perish which were published 10 years ago. Based on the literature used there are several medicinal plants that can be used as alternative medicine in the treatment of kidney failure.